0
$\begingroup$

Prove the identity $$\sqrt{17+2\sqrt{30}}-\sqrt{17-2\sqrt{30}}=2\sqrt{2}.$$ We have $$\left(\sqrt{17+2\sqrt{30}}-\sqrt{17-2\sqrt{30}}\right)^2=17+2\sqrt{30}-2\sqrt{17+2\sqrt{30}}\cdot\sqrt{17-2\sqrt{30}}+17-2\sqrt{30}=34-2\sqrt{(17)^2-(2\sqrt{30})^2}=34-2\sqrt{289-120}=34-2\sqrt{169}=34-2.13=8=(2\sqrt2)^2, $$ so $$\sqrt{17+2\sqrt{30}}-\sqrt{17-2\sqrt{30}}=2\sqrt{2}.$$ In the hints the authors have written that I should use the fact that the LHS is positive and square it. What would be the problem if it wasn't positive? The identity obviously won't hold because LHS<0, RHS>0...

$\endgroup$
9
  • 2
    $\begingroup$ You equated the squares of the LHS and RHS. To posit that LHS = RHS, you need to say they have the same sign. I think that's what the hint was about. $\endgroup$ – Stefan Lafon Apr 6 at 21:30
  • 1
    $\begingroup$ Oh, so I did show that $\text{LHS}^2=\text{RHS}^2$ but this can mean that $\text{LHS}=-\text{RHS}$ or vice versa? $\endgroup$ – Medi Apr 6 at 21:32
  • 3
    $\begingroup$ It is possible to show that $\sqrt{17 + 2\sqrt{30}} = \sqrt{15} + \sqrt{2}$ and that $\sqrt{17 - 2\sqrt{30}} = \sqrt{15} - \sqrt{2}$, from which the result follows. $\endgroup$ – N. F. Taussig Apr 6 at 21:33
  • 1
    $\begingroup$ @Medi Yes, that is true. You need the fact that both sides are positive to draw the conclusion that $\sqrt{17 + 2\sqrt{30}} - \sqrt{17 - 2\sqrt{30}} = 2\sqrt{2}$ from your calculations. $\endgroup$ – N. F. Taussig Apr 6 at 21:34
  • 4
    $\begingroup$ Does this answer your question? Show that $A=\sqrt{\left|40\sqrt2-57\right|}-\sqrt{\left|40\sqrt2+57\right|}$ is a whole number $\endgroup$ – lone student Apr 6 at 21:44
5
$\begingroup$

both of your original real numbers are roots of $$ x^4 - 34 x^2 + 169 $$

Standard bit for quartic with no cubic term and no linear, $$ (x^2 - 13)^2 - 8 x^2 = x^4 - 34 x^2 + 169 $$ $$ (x^2 - 13)^2 - (x \sqrt 8)^2 = x^4 - 34 x^2 + 169 $$

This becomes ( because a difference of squares) $$ (x^2 - x \sqrt 8 - 13)(x^2 + x \sqrt 8 - 13) $$ so that your numbersare two out of four values $$ \frac{\pm \sqrt 8 \pm \sqrt {60}}{2} $$ or $$ \pm \sqrt 2 \pm \sqrt {15} $$

This leads to checking $$ (\sqrt 2 + \sqrt {15} )^2 = 17 + 2 \sqrt{30} $$ along with $$ (-\sqrt 2 + \sqrt {15} )^2 = 17 - 2 \sqrt{30} $$

Your original expression is equal to $$ (\sqrt 2 + \sqrt {15} ) - (-\sqrt 2 + \sqrt {15} ) $$

$\endgroup$
2
$\begingroup$

Since the roots on the LHS get "annihilated", it makes very much sense to look for natural $m,n$ such that

\begin{eqnarray*} 17+2\sqrt{30} & = & \left(\sqrt n + \sqrt m\right)^2 & = & n + m + 2\sqrt{nm}\\ 17-2\sqrt{30} & = & \left(\sqrt n - \sqrt m\right)^2 & = & n + m - 2\sqrt{nm} \end{eqnarray*}

From this approach you get \begin{eqnarray*} n+m & = & 17\\ \sqrt{nm} & = & \sqrt{30} \end{eqnarray*}

Obviously $n = 15, m=2$ fit, hence

$$\sqrt{17+2\sqrt{30}}-\sqrt{17-2\sqrt{30}}= \sqrt{15}+\sqrt 2 - (\sqrt{15}-\sqrt 2)=2\sqrt{2}$$

$\endgroup$
2
  • $\begingroup$ Thank you for the response! May I ask you why if $17+2\sqrt{30}=\left(\sqrt{n}+\sqrt{m}\right)^2$ then $17-2\sqrt{30}=\left(\sqrt{n}\color{red}{-}\sqrt{m}\right)^2$ where $n$ and $m$ are the same natural numbers? $\endgroup$ – Medi Apr 7 at 10:44
  • $\begingroup$ @Medi At the beginning I do not know this. But I set up two equations to test, whether I can find such $m$ and $n$. The test is quick and turns out to be successful. So, I can find the solution without any further more complicated calculations. The motivation behind this quick test lies just in the binomial formula $(a \color{blue}{\pm} b)^2 = a^2+b^2\color{blue}{\pm} 2ab$. $\endgroup$ – trancelocation Apr 7 at 11:15

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.